Research on Rural Tourism Design in Zhejiang under Sustainable Cultural Development - Ouyang , Linxin; Tanyapirom , Sakesan; Suntrayuth, Rasa (International Journal of Sociologies and Anthropologies Science Reviews, 2023)
Background and Aim: Zhejiang Province of China is located in China’s East China Sea, is China’s ports in the province, the province’s famous fishing villages are known to fish a lot of unique marine location advantages formed distinctive fishermen’s living customs, but also gradually formed a rich and colorful fishing culture in Zhejiang. Therefore, the sustainable tourism development of Zhejiang fishing villages is closely related to the overall economic level of Zhejiang Province. By searching for the characteristics of fishing villages in Zhejiang Province, we create a suitable image design and model and develop and promote it, to promote the development of sustainable cultural tourism in beautiful villages. Materials and Methods: Based on the perspective of sustainable development, this paper analyses and integrates the characteristics of the "Chinese Fishing Village" in Zhejiang Province from three aspects through literature research, field survey, and questionnaire survey, applying the concept of sustainable development and the strategy of CI to design an image design and model of sustainable development that meets the requirements of the Chinese fishing village, and promote it to the life of the fishing village. The image design and model of sustainable development of the "Chinese fishing village" are designed and promoted to the life of the fishing village, and the visual image of the sustainable development concept is set up, which helps to disseminate the core concept and spirit of the concept, to enhance the influence of the fishing village and to design and promote the common sustainable cultural development of the fishing village. Results: The study found that the characteristics of the "Chinese fishing village" in Xiangshan County, Zhejiang Province, China, combined the resource base of fishing culture and art in the fishing village with the brand communication, and designed a sustainable development model to take fishing culture as the core of the development, develop fishing culture resources, do a good job of promoting the fishing culture and increase the development of cultural and creative products, to promote the sustainable cultural tourism development of the village. sustainable cultural tourism development. Conclusion: Based on the results of the study, this paper derives image designs and models that contribute to the development of sustainable cultural tourism in villages.